Negatywistyczna metafizyka unitarna Leszka Nowaka jako przykład współczesnego namysłu metafizycznego - Kiedrowski, Krzysztof (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
Speculation, i.e. thinking based on the pure concepts is characteristic of philosophical branch called metaphysics. In this paper I’m trying to show the main ideas and assumptions of contemporary Polish metaphysical conception by Leszek Nowak – negativistic unitarian metaphysics. It contains three blocks of statements: metaphilosophical, methodological and subject ones. Unitarian metaphysics is being developed systemically, with the application of the method of idealization and concretization, and deductive one. The most important ideas of this conception are: atributivism (attributes are the conclusive base (arche) of reality), negativism (reality is first of all negative) and plurality-of-worlds (there are many worlds).